Distribution Channel Structure for Competing Supply Chains with Price and Lead-Time Sensitive Demand - WU, Zhengping (Institutional Knowledge at Singapore Management University, 2013)
This paper studies distribution channel structure strategies (to centralize or decentralize) for two competing supply chains that sell substitutable products with price and lead-time sensitive demand. We find that centralization (decentralization) associates with itself a price (lead-time) advantage and a lead-time (price) disadvantage. As a result, price substitution and lead-time substitution have different impact on the equilibrium channel structure. Specifically, price substitution favors decentralization whereas lead-time substitution tends to result in centralization. Our results show that the equilibrium channel structure may critically depend on the game type (Bertrand vs. Cournot) and the pro t criterion (manufacturer pro t criterion vs. channel pro t criterion). In the Cournot model, centralization for both chains (CC) is always the only Nash equilibrium. In the Bertrand model, CC is still the only Nash equilibrium for the manufacturer pro t criterion. On the channel pro t criterion, however, the equilibrium channel structure changes with the relative intensity of price and lead-time substitution.